Echocardographic changes in anorexia nervosa: a pathophysiological adaptation or a disease?. (8th February 2021) - Toriello, F; Santangelo, G; Bursi, F; Epis, E; Tamagni, ME; Massironi, L; Bertelli, S; Benetti, A; Cattaneo, M; Carugo, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Anorexia nervosa (AN) is one of the most common form of eating disorders and it is a severe and potentially fatal disease with high rates of morbidity and mortality especially in the population aged 15-25 years. Cardiac involvement occurs in approximately 80% of patients with AN. Cardiovascular complications include changes in the autonomic regulation (increased vagal tone, bradycardia, orthostatic hypotension, syncope), arrhythmias, congestive heart failure and sudden death. Few reports have described, in small series, a variety of echocardiographic abnormalities including decreased cardiac mass, mitral valve prolapse, pericardial effusion and reduced left ventricular (LV) dimensions. No previous studies, however, examined if there is a change in these abnormalities with weight fluctuations. Purpose: To describe echocardiographic findings among male and female patients with AN and to examine the effect of weight gain on clinical and echocardiographic parameters. Methods: We performed a single center, retrospective, study of patients diagnosed with AN using the diagnostic and statistical manual of mental disorders, fifth edition (DSM-5). Clinical, laboratory and ECG-graphic data were obtained by reviewing each patient's medical records. Echocardiographic parameters were measured off-line. Results: The study population consisted of 81 patients, mean age 24.5 ± 11.6 years, 92.6% females. 75% showed an extreme AN degree. Mean body mass index (BMI) was 15.2 ± 2.1 kg/m2. Mean heart rate was 57.2 ± 12.7 beats per minute. Some patients showed right bundle branch block (7.4%) or prolonged QT interval (14.8%). Patients with BMI below the mean value had more often pericardial effusion, smaller LV mass and LV end-diastolic volume and thinner interventricular septum (all p < 0.05). However, when index to BSA, LV mass and volumes were within normal range in the 90% of the population. They also showed mitral valve abnormalities and low values of white blood cells and platelets. The presence of pericardial effusion was not related to inflammatory parameters or protein deficiency. For 39 patients echocardiographic exams at the highest and the lowest weight were available. With weight gain, there was an improvement in LV mass, interventricular septum thickness, pericardial effusion and an increase in white blood cells and platelet count. Conclusions: Our study showed that patients with AN have a specific echocardiographic pattern which seems to be proportional to the body size, suggesting a pathophysiological adaptation to the lack of substrates, hypothesis confirmed by the regression with weight gain. It is possible that pericardic effusion fills the gap left by mass loss.